Sensorless control strategy for brushless doubly fed reluctance generator under voltage flickering at point of common coupling - Manish Paul; Adikanda Parida; Anu Kumar Das (Institute of Advanced Engineering and Science, 2026)
The brushless doubly-fed reluctance generator (BDFRG) is widely used in grid-connected wind energy conversion systems (WECS). It has been observed that there is a continuous voltage flickering at the point of common coupling (PCC) between the BDFRG power terminals and the alternating current (AC) microgrids due to either the load variations or wind turbine output variations. Under such circumstances, sensorless control of BDFRG using the existing model reference adaptive system (MRAS) models exhibits erroneous active power output. This is because the variables selected in these models are directly or indirectly dependent on the voltage at the PCC. In this paper, a sensorless control mechanism for the BDFRG is proposed, which provides better performance in terms of control accuracy. Moreover, the planned scheme is insensitive to the parameter variations of the BDFRG. The performance of the planned system has been tested with a voltage flickering of 50% for 1 ms at the PCC. The stability test presented in this paper reveals that the model is robust and error-free against the noise disturbances. The planned system is implemented using proper simulations and a hardware platform with a practical BDFRG of 2.5 kW, and a dSPACE CP1104 module.